Improving Inventory Management Policies for Perishable Items in H Supermarket - Safira, Farhana; Utama, Akbar Adhi (Syntax Literate, 2024)
Effective inventory management can reduce costs, minimize waste, and ensure product availability, directly impacting a supermarket’s revenue and operational efficiency. This study aims to investigate and improve inventory management policies for perishable items at H Supermarket, located in Riau. The research addresses fluctuating revenue and the gap between target and actual profit by optimizing inventory management through different policies. It specifically addresses the challenges of managing inventory for bread and fruits, which contribute significantly to the supermarket's revenue but are prone to high levels of waste and stockouts due to their short shelf lives. The research employs both qualitative and quantitative methods, including interviews with key stakeholders and analysis of three years of sales data, to identify root causes of inventory inefficiencies. Two distinct inventory policies were analyzed: a continuous review system for bread and a periodic review system for fruits. The continuous review system allows for real-time inventory monitoring, enabling more responsive restocking processes. In contrast, the periodic review system schedules inventory checks at regular intervals, optimizing the balance between freshness and stock levels. The results indicate that the continuous review system significantly reduces total annual costs for bread by approximately 61.4%, while the periodic review system, with a five-day review period, effectively manages fruit inventory, reducing annual costs by 19.1%. The research underscores the importance of tailored inventory management strategies for different types of perishable items. It highlights the need for accurate inventory tracking systems and comprehensive staff training to ensure precise inventory records. The findings suggest that implementing these optimized inventory policies can substantially enhance operational efficiency and reduce waste.